2020
DOI: 10.1111/jch.13987
|View full text |Cite
|
Sign up to set email alerts
|

A cluster‐randomized study on the Risk Assessment and Management Program for home blood pressure monitoring in an older population with inadequate health literacy

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The add-on nurse-led risk assessment and intervention sessions contributed further through patient empowerment on self-care, including self-BP monitoring, smoking cessation, dietary modifications, physical activity, medication adherence and help-seeking behavior. 11 , 31 The potential contribution of these interventions might be proxied from the greater likelihood for RAMP-HT participants to be nonsmokers, and have all 5 CVD risks being at or below target values after 5 years. The strategic risk-stratified management also allowed for better care coordination and resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…The add-on nurse-led risk assessment and intervention sessions contributed further through patient empowerment on self-care, including self-BP monitoring, smoking cessation, dietary modifications, physical activity, medication adherence and help-seeking behavior. 11 , 31 The potential contribution of these interventions might be proxied from the greater likelihood for RAMP-HT participants to be nonsmokers, and have all 5 CVD risks being at or below target values after 5 years. The strategic risk-stratified management also allowed for better care coordination and resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a previous survey using the Nutrition Literacy Assessment Instrument scale showed that BMI was associated with nutrition literacy and dietary habits [ 68 ]. Compared with people in the Risk Assessment and Management Program (RAMP) in a cluster-randomized survey, BMI showed no significant changes and a significantly higher BP control rate [ 69 ]. Obesity is often associated with salt-sensitive hypertension [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a previous survey using the Nutrition Literacy Assessment Instrument scale showed that BMI was associated with nutrition literacy and dietary habits [70]. Compared with people in the Risk Assessment and Management Program (RAMP) in a cluster-randomized survey, BMI showed no signi cant changes and there was a signi cantly higher BP control rate [71]. Obesity is often associated with salt-sensitive hypertension [72].…”
Section: Discussionmentioning
confidence: 99%